Development of Computer Based Diagnostic Assessment Completed with Simple Harmonic Movement Material Remedial Program - Kurniawan, B R; Kusairi, S.; Puspita, D. A.; Kusumaningrum, R. W. (Jurnal Pendidikan Fisika Indonesia, 2021)
Research and development of computer-based assessment is carried out to overcome the shortcomings of conventional paper-based assessment. Development is carried out by focusing on the use of isomorphic questions and improvement programs. This computer-based assessment was developed with two levels of questions. At each level there are isomorphic questions that are used as a reference in providing feedback to students about their concepts understanding. At each level there is also video material that can be used as a source of student learning before students utilize the remedial program. This computer-based assessment has been tested on 31 third-year undergraduate students in Physics Education, Universitas Negeri Malang. The results of media and material validation and the results of limited trials indicate that the computer-based assessment produced is feasible to be applied in learning.